Internal Audit Effectiveness From External Auditors' Perspective: An Empirical Study From Libya - Khaled Ali S. Endaya (Universiti Sains Islam Malaysia, 2024)
This study investigates the impact of internal auditors' characteristics and internal audit department performance, as independent variables, on internal audit effectiveness. The study also examines the influence of organization members' support, as a moderating variable, on these relationships, which represents the first effort for that. The theoretical framework of this study is based on three theories, which are; agency theory, institutional theory, and communication theory. The main research question addressed by this study is whether internal auditor's characteristics and internal audit department performance enhance internal audit effectiveness indirectly through organization members support. A total of 550 Libyan external auditors were selected by using random sampling from a list of the Libyan Association of Accountants and Auditors (LAAA) registered in August 2010. The number of usable personally administered questionnaires was 243 responses, yielding at 44.18 percent response rate, Based on multiple regression analysis, the results indicated that the internal auditor's characteristics and internal audit department performance were significantly related to internal audit effectiveness. The findings revealed that organization members' support was a moderator variable. The findings showed statistically that senior management support had the ability to strengthen the relationship between variables of study while effective audit committee, statistically, had not. Overall, the findings of this study are expected ta provide Libyan organizations with the importance of tackling the issue of internal audit effectiveness, and to contribute in strengthening the capacity of internal auditing in Libyan organizations when the recommendations are implemented.